Marigold Herbarium Visuals As Scarf Motifs Created Using Screen Printing Technique - Andina Febrasari (Corak, 2022)
Making a herbarium is one of the science supports used to introduce the flora diversity. This herbarium is not only used in the field of taxonomy, but several artists have used the herbarium as a work of art. Various types of plant herbarium are used as basic concepts in creating works of art, one of which is the diversity of essential plants. This paper discusses an art creation inspired by a herbarium of one of the essential plants cultivated in Indonesia, i.e. one of the marigold specieses, namely Tagetes Erecta L.. The visualization of the herbarium of the Marigold Tagetes erecta L. plant was done on scarfs using screen-printing technique. The aims of this research were to provide a new visual alternative for scarf motifs and to introduce marigold Tagetes erecta L. as a plant with essential oil.